Research on Leakage Current Waveform Spectrum Characteristics of Artificial Pollution Porcelain Insulator - Fang, Chunhua; Tao, Yuning; Wang, Jianguo; You, Haixin; Cui, Yan; Zhou, Mi (Frontiers in Energy Research, 2021)
The surface discharge development processes of polluted porcelain insulators for power transmission lines are tightly related with the development of leakage current (LC), the characteristics of LC, the insulating condition and discharge intensity of the insulator surface have an important significance for revealing the contamination discharge state of insulators. In order to analyze the LC characteristics of porcelain insulators in the process of pollution flashover, artificial pollution flashover tests on porcelain insulators were conducted in the artificial fog cabinet , and the characteristics of LC waveforms in time-domain and frequency-domain were simultaneously measured and analyzed during the tests. The results indicated that the amplitude of LC, fundamental harmonic, the third harmonic and fifth harmonic had a strong correlation, the maximum of LC(Im), the rate of total harmonics(THD) and the phase difference of fundamental harmonic(θ) were used for the representation of the characteristics of the LC waveform. The LC has the characteristics of high amplitude, low proportion harmonic and small phase difference between the fundamental harmonic and voltage before the flashover occurrence. The test results provide effective reference for porcelain insulators in pollution flashover forecasting.